Knowledge regarding high-risk pregnancy among pregnant women attending an antenatal clinic in Hetauda, Nepal - Shrestha, Kopila; Karki Silwal, Sahara; Prajapati, Uma; Rai Koirala, Sita; Datheputhe, Parbati (Journal of Chitwan Medical College, 2024)
Background: Maternal mortality is high due to complication of pregnancy and childbirth. High risk pregnancy put the pregnant women, fetus and neonate in the state of jeopardy. To reduce complication of high-risk pregnancy, it is necessary to have knowledge about high-risk pregnancy and its prevention and management. This study was conducted to assess knowledge regarding high-risk pregnancy among pregnant women. Method: A descriptive cross-sectional study was conducted at Antenatal Out Patient Department of Hetauda Hospital, Makawanpur, Nepal in 2021. Non-probability purposive sampling technique was used among pregnant women who met the inclusion criteria. Calculated Sample size was 132 pregnant women. Ethical approval was obtained from Nepal Health Research Council. Face to face interview technique was used to collect data. The collected data were analyzed by using descriptive statistics such as frequency, percentage, mean, standard deviation and inferential statistics such as Chi-square test. Result: Among 132 respondents, majority 85(64.4%) had moderate level of knowledge regarding high-risk pregnancy followed by 30(22.7%) had inadequate level of knowledge and surprisingly only 17(12.9%) respondents had adequate level of knowledge regarding high-risk pregnancy. There was statistically significant association among duration of marriage (p-value 0.032) and gravida (p-value 0.013) with level of knowledge at 5% significant level. Conclusion: Only few respondents had adequate level of knowledge regarding high-risk pregnancy so awareness activities are required in antenatal outpatient department of each hospital where maternity services are provided.